2013
DOI: 10.1152/japplphysiol.01499.2012
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic leptin-receptor knockout mice show partial rescue of leptin resistance in diet-induced obesity

Abstract: Jayaram B, Pan W, Wang Y, Hsuchou H, Mace A, CornelissenGuillaume GG, Mishra PK, Koza RA, Kastin AJ. Astrocytic leptin receptor knockout mice show partial rescue of leptin resistance in diet-induced obesity. J Appl Physiol 114: 734 -741, 2013. First published January 17, 2013 doi:10.1152/japplphysiol.01499.2012.-To determine how astrocytic leptin signaling regulates the physiological response of mice to diet-induced obesity (DIO), we performed metabolic analyses and hypothalamic leptin signaling assays on astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(38 reference statements)
1
30
1
Order By: Relevance
“…Interestingly, ALKO showed less hyperleptinemia and GFAP expression than WT mice when HCD was supplied, although the differences between ALKO and WT mice were not seen when SD was supplied (Jayaram et al, 2013). They speculated that in the case of prolonged HCD, astrocytic LepRs became highly reactive to circulating concentrations of leptin, followed by astroglial activation and proinflammatory cytokine secretion, which eventually led to neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ALKO showed less hyperleptinemia and GFAP expression than WT mice when HCD was supplied, although the differences between ALKO and WT mice were not seen when SD was supplied (Jayaram et al, 2013). They speculated that in the case of prolonged HCD, astrocytic LepRs became highly reactive to circulating concentrations of leptin, followed by astroglial activation and proinflammatory cytokine secretion, which eventually led to neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that in the case of prolonged HCD, astrocytic LepRs became highly reactive to circulating concentrations of leptin, followed by astroglial activation and proinflammatory cytokine secretion, which eventually led to neuroinflammation. Neuroinflammation reduces sensitivity of neurons to leptin (leptin resistance), enhancing hyperleptinemia even more (Jayaram et al, 2013). This speculation is based on a series of pathological events in the hypothalamus that explain the impaired leptin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report shows that neonatal overnutrition increased body weight and leptin, affecting glial cells as GFAP, glucose, and glutamate transporter expression were increased in hypothalamus, further suggesting that physiological changes in metabolic state can modulate astrocyte functions (Fuente-Martin et al 2012). Moreover, astrocyte leptin receptor knockout mice showed less severe obesity than wild-type mice (Jayaram et al 2013). While much remains to be understood about the astrocyte role in energy homeostasis, it seems clear that these cells are key players in the CNS response to obesity.…”
Section: Astrocytes and Energy Homeostasismentioning
confidence: 99%
“…It has also been reported that DIO mice exhibit increased expression of functional astrocytic LEPR in the hypothalamic region, an effect that may play a role in the development of leptin resistance (Hsuchou et al 2009a). Indeed, loss of astrocytic Lepr under HFD conditions provides partial protection against developing disturbances in neuronal leptin signaling (Jayaram et al 2013).…”
Section: New Players In Energy Balance Controlmentioning
confidence: 99%